Analysis of peer effects on consumption in rural China based on social networks. Issue 6 (1st February 2023) - Yang, Jisheng; Li, Jiaolong; Cao, Yanjun
ABSTRACT: This study empirically analyses peer effects on daily essential consumption and social related expenditure in rural China, where clan clustering often characterizes villages. The proportion of peer effects and autonomous behaviour in households' consumption behaviour is estimated by quasi-maximum likelihood estimation of the spatial autoregressive model, which includes the differences in characteristics between the household and its peers. It shows that, households put more weight on peer effects in daily essentials consumption, whereas more weight is put on autonomous behaviour in social related expenditure. In addition, peer effects may be significantly overestimated, especially for clothing and human affairs expenditure, if the differences in characteristics between the household and its peers are not considered.